KORELASI ANTARA MINAT MEMBACA DAN KEMAMPUAN MENGARANG PADA MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Nurcahyanti Nurcahyanti; Arza Aibonotika; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to see the relationship between reading interest and writing ability at students class 2019 of Japanese Language Education Study Program Universitas Riau. The sample in the research consisted of 26 respondents who were the entire population. The instruments in this research were a reading interest questionnaire and a student's writing ability test. The next data is based on the next prerequisite for normality and homogeneity, and hypothesis testing is carried out. From the results of hypothesis testing obtained a significance value of 0.158 > 0.05. On that basis of the Ho hypothesis is accepted and the Ha hypothesis is rejected, which means that there is no significant relationship between reading interest and writing ability at studdent class 2019 of students Japanese Language Education Study Program, Universitas Riau.Key Words: Reading, Reading Interest, Writing Ability